2016
DOI: 10.1021/acs.inorgchem.6b00653
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Ligand to Modulate the Magnetic Anisotropy in a Carboxylate-Bridged Dy2 Single-Molecule Magnet System

Abstract: A series of dinuclear Dy(III) compounds with the general formula [Dy2(μ2-anthc)4(anthc)2(L)2] (anthc(-) = 9-anthracenecarboxylate, L = 2,2'-bipyridyl (1), 1,10-phenanthroline (2), and 4,7-dimethyl-1,10-phenanthroline (3)) were synthesized and magnetically characterized. These compounds exhibit single-molecule magnet (SMM) behavior in the absence of the direct-current field, which is rarely observed for carboxylate-bridged dinuclear Dy2 system. With the first coordination sphere of Dy(III) centers being fixed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(47 citation statements)
references
References 49 publications
4
41
0
2
Order By: Relevance
“…[27][28][29] Although difficult, it has been showed that the magnetic interactions are extremely sensitive to the subtle variations of the local coordination sphere and the ligand field around the dysprosium (III) ion. [30][31] A current challenge, therefore, is to assemble targeted polynuclear dysprosium (III) 4 SMMs, thereby providing a means of tuning the magnetic interactions through the influence of different coordination environments around the metal site.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Although difficult, it has been showed that the magnetic interactions are extremely sensitive to the subtle variations of the local coordination sphere and the ligand field around the dysprosium (III) ion. [30][31] A current challenge, therefore, is to assemble targeted polynuclear dysprosium (III) 4 SMMs, thereby providing a means of tuning the magnetic interactions through the influence of different coordination environments around the metal site.…”
Section: Introductionmentioning
confidence: 99%
“…The example of 1 clearly shows a Dy 2 node with potential to be an SMM actually showing the SMM property in the MOF. Similar Dy 2 units have been reported to be SMMs but they often have monoatomic oxygen bridges from syn, anti ‐carboxylate bridging groups and chelating bpy or phen ligands . In fact researchers have shown that these chelating ligands can be used to fine tune the crystal field and have a large effect in the SMMs properties of the Dy 2 unit.…”
Section: Resultsmentioning
confidence: 77%
“…On the other hand, chelating ligands could block two or three coordination sites per Ln III ion, thereby preventing potential polymerization . For this purpose, N‐donor species such as 2,2′‐bipyridine, 1,10‐phenanthroline, or 2,2′:6′,2′′‐terpyridine are ideal candidates …”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the analogous lanthanum complex [La 2 (µ 2 ‐9‐AC) 4 (9‐AC) 2 (bpy) 2 ] has previously been published . Moreover, recently, Zhang and Liu and co‐workers reported the analogous dysprosium SMM compound [Dy 2 (µ 2 ‐9‐AC) 4 (9‐AC) 2 (bpy) 2 ] in order to study the magnetic dependence on the variation of the chelating N‐donor ligand . We wished to expand on these previous works by using other lanthanide ions in the search for multifunctional complexes displaying magnetic and luminescent properties.…”
Section: Introductionmentioning
confidence: 99%